2017
DOI: 10.1186/s12943-017-0688-6
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic miR-210-3p promotes prostate cancer cell EMT and bone metastasis via NF-κB signaling pathway

Abstract: BackgroundThe primary issue arising from prostate cancer (PCa) is its high prevalence to metastasize to bone, which severely affects the quality of life and survival time of PCa patients. miR-210-3p is a well-documented oncogenic miRNA implicated in various aspects of cancer development, progression and metastasis. However, the clinical significance and biological roles of miR-210-3p in PCa bone metastasis remain obscure.MethodsmiR-210-3p expression was evaluated by real-time PCR in 68 bone metastatic and 81 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
173
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(181 citation statements)
references
References 71 publications
2
173
0
Order By: Relevance
“…Furthermore, several lines of evidence reported that NF-κB signaling plays a critical role in the bone metastasis of cancers [37, 41]. Park et al [42] found that NF-κB signaling promoted the bone resorption characteristics of osteolytic bone metastasis in breast cancer cells via upregulating granulocyte macrophage-colony stimulating factor expression that promoted osteolytic bone metastasis by stimulating osteoclast development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several lines of evidence reported that NF-κB signaling plays a critical role in the bone metastasis of cancers [37, 41]. Park et al [42] found that NF-κB signaling promoted the bone resorption characteristics of osteolytic bone metastasis in breast cancer cells via upregulating granulocyte macrophage-colony stimulating factor expression that promoted osteolytic bone metastasis by stimulating osteoclast development.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a key step toward cancer metastasis . Wnt, TGF‐β, Notch, NF‐κB, and MAPK/ERK have been implicated as the key pathways involved in EMT process. Several lncRNAs participate in EMT process .…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In this study, a novel lncRNA, lncRNA DRHC, was shown to be EMT is a key step toward cancer metastasis. 26 Wnt, 27 TGF-β, 28,29 Notch, 30,31 NF-κB, 32,33 and MAPK/ERK 34 have been implicated as the key pathways involved in EMT process. Several lncRNAs participate in EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for U6 and miR‐324‐5p were purchased from RiboBio. The specific process of qRT‐PCR was described in our previous study (Ren et al , ). The detailed information of primers is presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…All mouse experiments were approved by the Institutional Animal Care and Use Committee of Sun Yat‐sen University and performed as previously described (Ren et al , ). Ten mice were used in every group for animal experiments.…”
Section: Methodsmentioning
confidence: 99%